Optimization of Device Installations in the Home Solar Power Generation System - Ignatius R Mardiyanto; Sri Paryanto Mursid; Sri - Utami (Jurnal Internasional Penelitian Teknologi Terapan, 2022)
One of the main challenges in building a Solar Power Generation System at home or a Home Solar Power Plant (Home SPP) is choosing component specifications according to price. The main components of Home SPP are photovoltaics (PV) panels, inverters, and wiring systems. Given the strict price constraints, the selection of parts available on the commercial market is generally of low quality. However, low-quality components can still provide a significant advantage by optimizing the plant design. This research proves that the proper configuration can reduce electricity bills by 52.2%. This configuration does by choosing a Grid Tie Inverter (GTI) with a high working voltage and a 12 Volt PV configured in a parallel series circuit to work at 24 Volts. In addition, the 12 Volt PV panels configured in series to 24 Volts are proven to increase the conversion efficiency.